Adapting to a Finnish workplace : case : occupational immigration of Chinese metal workers. - Korkalainen, Maija (2009)
The aim of the study was to investigate intercultural adaptation of occupational immigrants to Finnish working life and culture and identify factors that support or hinder the adaptation process. Due to demographic changes in the society and the increasing number of foreigners in Finnish workplaces, the study of occupational immigration is a very contemporary topic.